Pi in the sky eaudiobook - Mass, Wendy (Recorded Books Inc., 2013)
New York Times bestselling author Wendy Mass has received an array of awards for her children's fiction, including the ALA Schneider Family Book Award. Pi in the Sky stars Joss, the seventh son of the Supreme Overlord of the Universe, whose job is to deliver magical pies—ones that happen to hold the secrets of the cosmos. But when planet Earth suddenly disappears, Joss must figure out a way to bring it back—even if it means enlisting the help of an outspoken Earth girl named Annika.